2016
DOI: 10.1098/rsos.160840
|View full text |Cite
|
Sign up to set email alerts
|

Does the stress response predict the ability of wild birds to adjust to short-term captivity? A study of the rock pigeon ( Columbia livia )

Abstract: Although the transfer of wild animals to captivity is crucial for conservation purposes, this process is often challenging because some species or individuals do not adjust well to captive conditions. Chronic stress has been identified as a major concern for animals held on long-term captivity. Surprisingly, the first hours or days of captivity have been relatively overlooked. However, they are certainly very stressful, because individuals are being transferred to a totally novel and confined environment. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Although we did not measure food consumption or energy expenditure, we found that plasma CORT levels increased after 24 h in captivity. This result is consistent with the reduced weight and elevated baseline CORT observed in captive, wild-caught Chukar (Alectoris chukar) ), increased CORT levels and reduced body weight after 4-10 h of fasting in the Zebra Finch (Taeniopygia guttata) (Lynn et al 2010), and in Rock Pigeons (Columbia livia) after 24 h in captivity (Angelier et al 2016). Reduced body weight is a hallmark of the elevated baseline CORT (Sapolsky et al 2000) secreted in response to the chronic stress associated with captivity, e.g., confinement, altered light conditions and diet (Morgan and Tromborg 2007).…”
Section: Effects Of 24-h Captivity Stresssupporting
confidence: 85%
See 2 more Smart Citations
“…Although we did not measure food consumption or energy expenditure, we found that plasma CORT levels increased after 24 h in captivity. This result is consistent with the reduced weight and elevated baseline CORT observed in captive, wild-caught Chukar (Alectoris chukar) ), increased CORT levels and reduced body weight after 4-10 h of fasting in the Zebra Finch (Taeniopygia guttata) (Lynn et al 2010), and in Rock Pigeons (Columbia livia) after 24 h in captivity (Angelier et al 2016). Reduced body weight is a hallmark of the elevated baseline CORT (Sapolsky et al 2000) secreted in response to the chronic stress associated with captivity, e.g., confinement, altered light conditions and diet (Morgan and Tromborg 2007).…”
Section: Effects Of 24-h Captivity Stresssupporting
confidence: 85%
“…Bringing free-living animals into captivity is frequently required for conservation, and for research in animal ecology, environmental physiology, and conservation biology (Dickens et al 2010;Mason 2010;Mason et al 2013;Dickens and Bentley 2014). This process subjects animals to both the acute stress of immediate capture and the chronic stress of captivity, resulting in the alteration of normal physiology and behavior (Dickens et al 2010;Angelier et al 2016). In vertebrates, capture stress may acutely activate the hypothalamic-pituitary-adrenal (HPA) axis to increase glucocorticoid (GC) levels that can enhance survival by regulating behavioral and physiological responses (Romero and Wingfield 1999;Sapolsky et al 2000;Wingfield and Kitaysky 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals taken from the wild should only be held in captivity where completely necessary—if the aim is not to form a captive population—for a duration that allows their safe release. The process of bringing animals into captivity, for example, transportation (Box 4), exposes individuals to multiple stressors that can lead to significant initial stress and extended changes to the stress‐coping mechanisms that can allow adjustment to captivity (Adams, Farnworth, Rickett, Parker, & Cockrem, 2011; Angelier, Parenteau, Trouve, & Angelier, 2016). Researchers should not underestimate the difficulty of designing sets of captive conditions for different species (Schmidt, 2010; Box 5).…”
Section: Welfare Considerations In Capturing Handling and Housing Ofmentioning
confidence: 99%
“…However, these "common-to-the-zoo and not-yet-of-conservation-concern species" are still relevant to the development of avicultural practice, as they can serve as excellent models for testing and trialing key aspects of animal care needed for similar species that do require conservation planning and action. For example, trialing the resilience of, or illustrating the physiological changes that may occur in, captively housed populations of threatened species destined for wild reintroduction, but in a commonly housed experimental population [8], provides useful details on developing conservation-promoting husbandry routines for threatened species. These conservation surrogates can also be used in public relations efforts [9], to promote the reasons for the conservation work, the relevance of conservation action and to explain how management of ex situ individuals helps those in the wild.…”
Section: Introductionmentioning
confidence: 99%